"Accidental" urban wetlands: ecosystem functions in unexpected places. Issue 5 (15th May 2017) - Palta, Monica M; Grimm, Nancy B; Groffman, Peter M
Abstract : "Accidental" urban wetlands are formed not through deliberate restoration or management activity, but as a product of land use and water infrastructure decisions by municipalities. Often formed in abandoned industrial, residential, or low‐lying commercial areas, where overland flows from storms and municipal water use accumulate, these ecosystems support wetland soils and plant communities. Research that we have conducted in the northeastern and southwestern US suggests that accidental wetlands are capable of counteracting anthropogenic eutrophication, providing habitats for important ecological communities, fostering biodiversity, and mitigating heat. Because the factors contributing to their formation are ubiquitous, accidental wetland systems are likely pervasive in urban landscapes, accounting for a substantial portion of aquatic habitat extent and influencing nutrient and water cycles within cities. They also provide ecosystem services at a fraction of the cost associated with more traditional environmental management efforts.